The Effectiveness of Therapeutic Communities in the Treatment of Addicts With Antisocial Personality Disorder: A Critical Review of the Literature - Herath, Senanayake Mohan (Auckland University of Technology, 2015)
This dissertation explores the links between antisocial personality disorder (ASPD) and addictions, and the usefulness of treatment through modified therapeutic communities (TCs). It critically reviews and synthesises the literature in the areas of ASPD, addicts with ASPD, and TCs treating addictions. The review identifies a number of themes emerging from the literature; similarities in the behaviour of individuals with ASPD and addicts, difficulties in diagnosing ASPD, gender differences, difficulties of treating co-occurring disorders, and the effectiveness of particular treatment options including therapeutic communities. The review concludes with a number of guidelines for clinicians, which include important structures and modalities to be considered in the treatment of addicts with ASPD in therapeutic community settings.
Keywords: Therapeutic communities; Antisocial personality; ASPD; Addicts; Treatment of addicts with antisocial personality disorder; Therapeutic communities in the treatment of addicts with antisocial personality disorder; Conduct disorder; Modified therapeutic communities; TC